Tantangan dan Solusi Pengembangan Ar-Rahn BSI KC Gresik Kartini - Nugraha, Raniah Tasya; Lilik Rahmawati (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2022)
Background. The community needs a source of financing that is fast, easy, safe and in accordance with sharia. BSI opens sharia gold pawn services (rahn) with various internal and external challenges.Aim. This study aims to examine the real challenges faced by BSI in the development of sharia gold pawning (rahn) and their solutions.Methods. The researcher used a qualitative research design with a phenomenological study paradigm. The data were collected through unstructured interviews, documentation, and observation. Participants were selected purposively based on the emic perspective. The research data were analyzed using a phenomenological data analysis model.Results. In rahn, there is no term